Effect of High Hydrostatic Pressure on Human Trabecular Bone Regarding Cell Death and Matrix Integrity - Waletzko-Hellwig, Janine; Pohl, Christopher; Riese, Janik; Schlosser, Michael; Dau, Michael; Engel, Nadja; Springer, Armin; Bader, Rainer (Frontiers in Bioengineering and Biotechnology, 2021)
The reconstruction of critical size bone defects is still clinically challenging. Even though the transplantation of autologous bone is used as gold standard, this therapy is accompanied by do-nor site morbidities as well as tissue limitations. The alternatively used allografts, which are devi-talized due to thermal, chemical or physical processing, often lose their matrix integrity and have diminished biomechanical properties. High Hydrostatic Pressure (HHP) may represent a gentle alternative to already existing methods since HHP treated human osteoblasts undergo cell death and HHP treated bone cylinders maintain their mechanical properties. The aim of this study was to determine whether HHP treatment of trabecular bone blocks causes necrotic or apoptotic cell death. Therefore, different pressure protocols (250 MPa and 300 MPa for 10, 20 and 30 min) and end point analysis such as quantification of DNA-fragmentation, gene expression, SDS-PAGE, FESEM analysis and histological staining were performed. While both protein and matrix integ-rity was preserved, molecular biological methods showed an apoptotic differentiation of cell death for lower pressures and shorter applications (250 MPa for 10 and 20 min) and necrotic dif-ferentiation for higher pressures and longer applications (300 MPa for 30 min). This study sug-gests HHP as a favorable alternative to existing physical-chemical devitalizing processings.